2017
DOI: 10.5380/ce.v22i3.50238
|View full text |Cite
|
Sign up to set email alerts
|

Estresse Ocupacional E Fatores Associados Entre Enfermeiros De Hospitais Públicos

Abstract: RESUMO: Objetivou-se avaliar o estresse ocupacional e fatores associados entre enfermeiros de hospitais públicos. Estudo transversal com amostra de 185 enfermeiros de três hospitais públicos do Paraná. Os dados foram coletados entre novembro de 2015 e abril de 2016, mediante questionário de caracterização dos participantes e a Job Stress Scale. Realizaram-se análises descritivas e regressão logística. Entre os participantes, predominou o trabalho passivo e o de alta exigência. A percepção negativa dos serviços… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 28 publications
1
7
0
23
Order By: Relevance
“…According to the final logistic regression model, professionals who receive lower support from bosses and co-workers have 3.60 more chances of exposure to stress than those with high social support. Such data is corroborated by findings from a study conducted in public hospitals in southern Brazil, in which was observed that the higher the perception of social support received, the less reports of exhausting work (9) .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…According to the final logistic regression model, professionals who receive lower support from bosses and co-workers have 3.60 more chances of exposure to stress than those with high social support. Such data is corroborated by findings from a study conducted in public hospitals in southern Brazil, in which was observed that the higher the perception of social support received, the less reports of exhausting work (9) .…”
Section: Discussionsupporting
confidence: 65%
“…The nursing profession stands out among those vulnerable to the development of occupational stress. These professionals are directly responsible for the care provided to patients, organization of the hospital department and for various administrative and bureaucratic activities (9) . Nursing is one of the most exposed professions to the risk of tension and illness within the hospital institution, because professionals face inadequate working conditions in an unhealthy environment with work overload and repetition of tasks (10) .…”
Section: Introductionmentioning
confidence: 99%
“…As condições de trabalho da equipe de enfermagem não são satisfatórias em quase todos os países do mundo, o que também pode ser um risco que contribui para o surgimento de patologias, gerando dor. Essas condições podem ter influência da remuneração inadequada, a carga horária muito longa sem período de descanso, plantões, tipo de horário, categoria profissional e a quase impossibilidade de ascensão na carreira profissional 21,22 .…”
Section: Discussionunclassified
“…No intuito de se atingir um senso, propôs-se que a população de estudo estivesse composta por todos (n=104) os enfermeiros pertencentes à instituição na época do estudo. (1)(2)(3)(4) , em nível de concordância (10) .…”
Section: População Do Estudounclassified